2007
DOI: 10.1002/jms.1278
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric integrated selective enrichment target (ISET) for solid‐phase‐based sample preparation in MALDI–TOF MS

Abstract: A polymer microfabricated proteomic sample preparation and MALDI MS sample presentation device, the integrated selective enrichment target (ISET), comprising an array of perforated nanovials is reported. Each perforated nanovial can be filled with selective extraction media (microbeads) for purification and concentration of protein/peptides prior to matrix-assisted laser desorption/ionization mass spectrometry (MALDI MS). The main areas covered are the influence of the molding-process-induced surface roughness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…The microfabricated proteomic sample handling platform, Integrated Selective Enrichment Target (ISET), previously described by our group has been demonstrated to provide improved performance in solid-phase extraction (SPE) sample preparation [34, 35]. The benefits of the ISET are high sensitivity in the purification/concentration step of obtained peptides and low absorptive sample losses as all sample preparation steps are performed on the same platform.…”
Section: Introductionmentioning
confidence: 99%
“…The microfabricated proteomic sample handling platform, Integrated Selective Enrichment Target (ISET), previously described by our group has been demonstrated to provide improved performance in solid-phase extraction (SPE) sample preparation [34, 35]. The benefits of the ISET are high sensitivity in the purification/concentration step of obtained peptides and low absorptive sample losses as all sample preparation steps are performed on the same platform.…”
Section: Introductionmentioning
confidence: 99%
“…This effect is based on the affinity of the dissolved sample to stay in the solvent and the variability in drying. Trimpin and coworkers [22] have shown that the latter limitation can be overcome by the use of a solvent-free sample preparation method, which has already been proven valuable in several applications [14,[16][17][18][19][20][21][22]. In addition, a few experiments were made concerning the possibility to quantify certain synthetic polymers [14,[23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In this approach, microscale cavities in the target plate surface are filled with solid-phase extraction media and serve for purification as well as concentration of peptides prior to MALDI-MS (Ekström et al, 2006). The method based on polymeric integrated selective enrichment target (ISET) was further extended and optimized (Ekström et al, 2007).…”
Section: On-plate Sample Extractionmentioning
confidence: 99%